Financial management : theory & practice / Eugene F Brigham; Michael C Ehrhardt - Brigham, Eugene F.1930-
This book emphasizes actions that a manager can and should take to increase the intrinsic value of the firm. It begins with fundamental concepts, including background on the economic and financial environment, financial statements (with an emphasis on cash flows), the time value of money, bond valuation, risk analysis, and stock valuation. With this background, it further discusses how specific techniques and decision rules can be used to help mazimize the value of the firm.